Role of benzalkonium chloride surface preconditioning in the increased resistance of biofilms to removal and disinfection - Pereira, Maria Olívia (2006)
The main goals of the present study was to ascertain the role of surface preconditioning in the biofilm sanitation (removal and disinfection) ability of the cationic surfactant benzalkonium chloride (BC) and to investigated whether BC preconditioning can be a factor of the increased resistance of the Pseudomonas fluorescens biofilms to the surfactant. Prior to biofilm formation, coupons of two distinct materials (stainless steel and silicone rubber) currently used on medical and industrial processing facilities were exposed to several sub-effective concentrations of BC for 30 min. Afterwards, these conditioned coupons were used as the surfaces to form biofilms in a chemostat for 6 days. The antimicrobial action of BC on the biofilms was assessed by means of respiratory activity, due to oxygen consumption, and biofilm mass. The results showed that BC preconditioning, by itself, did not prevent or impair biofilm formation. In general, the mass and respiratory activity of the biofilms developed on the conditioned coupons increased with the increase of the BC concentration used in the preconditioning. The data related with BC application to the bacterial biofilms formed on the conditioned metal and rubber coupons showed that biofilms became more difficult to inactivate, especially those that have been developed in the coupons preconditioned with the higher BC concentrations. Thus, it can be concluded that the antimicrobial ability of BC was considerably disturbed when the surfaces are preconditioned with the surfactant. Based merely on this data, it can be speculated that, in the initial adhesion stage, the contact of the P. fluorescens with the BC residues adsorbed on the coupons surface, due to preconditioning, induces bacteria resistance when they are entrapped in a developed biofilm and submitted to BC aggression.